Unique features of regulation of sulfate assimilation in monocots. (12th September 2022) - Rahimzadeh Karvansara, Parisa; Kelly, Ciaran; Krone, Raissa; Zenzen, Ivan; Ristova, Daniela; Silz, Emely; Jobe, Timothy O; Kopriva, Stanislav
Abstract: Sulfate assimilation is an essential pathway of plant primary metabolism, regulated by the demand for reduced sulfur (S). The S-containing tripeptide glutathione (GSH) is the key signal for such regulation in Arabidopsis, but little is known about the conservation of these regulatory mechanisms beyond this model species. Using two model monocot species, C3 rice ( Oryza sativa ) and C4 Setaria viridis, and feeding of cysteine or GSH, we aimed to find out how conserved are the regulatory mechanisms described for Arabidopsis in these species. We showed that while in principle the regulation is similar, there are many species-specific differences. For example, thiols supplied by the roots are translocated to the shoots in rice but remain in the roots of Setaria . Cysteine and GSH concentrations are highly correlated in Setaria, but not in rice. In both rice and Setaria, GSH seems to be the signal for demand-driven regulation of sulfate assimilation. Unexpectedly, we observed cysteine oxidation to sulfate in both species, a reaction that does not occur in Arabidopsis. This reaction is dependent on sulfite oxidase, but the enzyme(s) releasing sulfite from cysteine still need to be identified. Altogether our data reveal a number of unique features in the regulation of S metabolism in the monocot species and indicate the need for using multiple taxonomically distinct models to better understand the control of nutrient homeostasis, which is important for generating low-input crop varieties. Abstract : Investigating demand-driven regulation of sulfate assimilation in rice and Setaria viridis, we revealed that in contrast to Arabidopsis, both species are able to oxidize cysteine to sulfate.